Network analysis of sport-related concussion research during the past decade (2010-2019) - Eagle, S. R.; Kontos, A. P.; Collins, M. W.; Connaboy, C.; Flanagan, S. D. (Journal of Athletic Training, 2021)
Context: Research into sport-related concussion (SRC) has grown substantially over the past decade, yet no authors to date have synthesized developments over this critical time period. Objective: To apply a network-analysis approach in evaluating trends in the SRC literature using a comprehensive search of original, peer-reviewed research articles involving human participants published between January 1, 2010, and December 15, 2019. Design: Narrative review. Main Outcome Measure(s): Bibliometric maps were derived from a comprehensive search of all published, peer-reviewed SRC articles in the Web of Science database. A clustering algorithm was used to evaluate associations among journals, organizations or institutions, authors, and key words. The online search yielded 6130 articles, 528 journals, 7598 authors, 1966 organizations, and 3293 key words. Results: The analysis supported 5 thematic clusters of journals: (1) biomechanics/sports medicine (n = 15), (2) pediatrics/rehabilitation (n = 15), (3) neurotrauma/neurology/neurosurgery (n = 11), (4) general sports medicine (n = 11), and (5) neuropsychology (n = 7). The analysis identified 4 organizational clusters of hub institutions: (1) University of North Carolina (n = 19), (2) University of Toronto (n = 19), (3) University of Michigan (n = 11), and (4) University of Pittsburgh (n = 10). Network analysis revealed 8 clusters for SRC key words, each with a central topic area: (1) epidemiology (n = 14), (2) rehabilitation (n = 12), (3) biomechanics (n = 11), (4) imaging (n = 10), (5) assessment (n = 9), (6) mental health/chronic traumatic encephalopathy (n = 9), (7) neurocognition (n = 8), and (8) symptoms/impairments (n = 5). Conclusions: The findings suggest that during the past decade, SRC research has (1) been published primarily in sports medicine, pediatric, and neuro-focused journals, (2) involved a select group of researchers from several key institutions, and (3) concentrated on new topical areas, including treatment or rehabilitation and mental health.